2022
DOI: 10.2355/isijinternational.isijint-2021-338
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spheroidizing Treatment on the Graphite and Mechanical Properties of Cast High-nickel Austenitic Ductile Iron

Abstract: Cast high-nickel austenitic ductile iron (CHNADI) is widely used in high temperature, low temperature and strong corrosive environments due to its good comprehensive mechanical properties. However, its low yield strength limits its application in nuclear power equipment. Herein, the influence of nodularizer and processing temperature on the graphite and mechanical properties of CHNADI was investigated to significantly promote its properties. With the increase of nodularizer dosage, the mechanical properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…It was reported that through appropriate heat treatment processes, the impact toughness of ductile iron under low-temperature conditions can be markedly enhanced, thereby avoiding the brittle fracture. This innovative approach can make much wider applications for ductile iron [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that through appropriate heat treatment processes, the impact toughness of ductile iron under low-temperature conditions can be markedly enhanced, thereby avoiding the brittle fracture. This innovative approach can make much wider applications for ductile iron [16][17][18].…”
Section: Introductionmentioning
confidence: 99%